Methanol Conversion into Dimethyl Ether on the Anatase TiO2(001) Surface. (23rd November 2015) - Xiong, Feng; Yu, Yan‐Yan; Wu, Zongfang; Sun, Guanghui; Ding, Liangbing; Jin, Yuekang; Gong, Xue‐Qing; Huang, Weixin
Abstract: Exploring reactions of methanol on TiO2 surfaces is of great importance in both C1 chemistry and photocatalysis. Reported herein is a combined experimental and theoretical calculation study of methanol adsorption and reaction on a mineral anatase TiO2 (001)‐(1×4) surface. The methanol‐to‐dimethyl ether (DME) reaction was unambiguously identified to occur by the dehydration coupling of methoxy species at the fourfold‐coordinated Ti 4+ sites (Ti4c ), and for the first time confirms the predicted higher reactivity of this facet compared to other reported TiO2 facets. Surface chemistry of methanol on the anatase TiO2 (001)‐(1×4) surface is seldom affected by co‐chemisorbed water. These results not only greatly deepen the fundamental understanding of elementary surface reactions of methanol on TiO2 surfaces but also show that TiO2 with a high density of Ti4c sites is a potentially active and selective catalyst for the important methanol‐to‐DME reaction.